Characterization of obsidian from the Tibetan Plateau by XRF and NAA. (February 2016) - Perreault, Charles; Boulanger, Matthew T.; Hudson, Adam M.; Rhode, David; Madsen, David B.; Olsen, John W.; Steffen, Martina L.; Quade, Jay; Glascock, Michael D.; Brantingham, P. Jeffrey
Abstract: The Tibetan Plateau is the highest contiguous terrain on the planet. It is cold, dry, poor in oxygen, and one of the last habitats to have been colonized by our species. Here we present the first quantitative chemical characterization of obsidian artifacts from the Tibetan Plateau. The artifacts in our sample come from 20 archeological sites spanning a large portion of the northeast and the southwest regions of the Plateau. We find that five varieties of obsidian were used at these sites. We also identify the geological source of one of the obsidian varieties as near Balung Tso in south-central Tibet. The five varieties of volcanic glass are distributed into two discrete zones in the northeast and the southwest of Tibet, suggesting that the two regions may have been occupied independently, and that interactions between them were limited. Finally, we also find that some of the transportation distances of obsidian are several hundred kilometers long. Highlights: First chemical characterization of obsidian artifacts from the Tibetan Plateau Five distinct varieties of obsidian identified Obsidian varieties are distributed into two discrete geographic zones Obsidian transportation distances of hundreds of kilometers